Tourists' Satisfaction Towards Tourism Logistics Management Influencing Loyalty on Tourists of Phitsanulok Province - Passa, Kamonsak; Ponanan, Klairung (Journal of Industrial Business Administration, 2024)
This research aims to study components of tourism logistics management influencing loyalty tourists to tourist attractions in Muang District, Phitsanulok Province. Based on the aims of this research, the results of the study can be applied to the development plan for tourism logistics management, which can help to increase the number of tourists in Phitsanulok Province. Additionally, the income of the tourism industry can be increased. In this study, the components of tourism logistics management are investigated as the factors that influence tourists. The factors consist of physical flow, information flow, financial flow, facilitating infrastructure, and sustainability. These factors have been used for data collection with the questionnaire for analyzing the tourists' satisfaction towards tourism logistics management influencing loyalty on tourists of Phitsanulok Province. The data has been collected from the tourists in Muang District, Phitsanulok Province with a sample size of 400 samples. The data was analyzed by using Multiple Regression Analysis. The results show that information flow, financial flow,facilitating infrastructure, and sustainability have a statistically significant influence on loyalty tourists with a significance level of 0.05.